Protective assessment of cimetidine against cyclophosphamide-induced kidney injury - Adikwu, Elias; Bokolo, Bonsome (Asian Journal of Medical Sciences, 2018)
Background: Nephrotoxicity is one of the frequent toxicities observed with cyclophosphamide (CP) use which may involve oxidative stress. Cimetidine is an antihistamine with anti-oxidative stress activity. Aims and Objectives: The study aimed to evaluate the effect of cimetidine on cyclophosphamide-induced kidney damage in albino rats. Materials and Methods: Forty eight adult rats randomised into 8 (A-H) groups of 6 rats per group were experimentally used for this study.Group A (control) was treated with water, while groups B-D were treated with 5, 10 and 20 mg/kg of cimetidine intraperitoneally (ip) daily for 5 days respectively. Group E was treated with150 mg/kgof CP ip on the 5th day. Groups F-H were pretreated with 5, 10 and 20 mg/kg cimetidine ip daily for 5 days and treated with CP ip on the 5th day respectively. Rats were sacrificed serum was extracted from blood and evaluated for renal function markers, while kidneys were harvested and evaluated for oxidative stress markers and histology. Results: There were no significant effects (p>0.05) on the body and kidney weights of CP-treated rats. However, impaired kidney functions in CP-treated rats were marked by significant (p<0.05) increases in creatinine, urea, uric acid, sodium, potassium, chloride, bicarbonate, and malondialdehyde levels when compared to control. On the other hand, significant (p<0.05) decreases in superoxide dismutase, catalase, glutathione, glutathione peroxidase, total protein and albumin were obtained in CP-treated rats when compared to control. Necrotic changes were observed in the kidneys of CP-treated rats. However, CP-induced nephrotoxic effects were significantly (p<0.05; 0.01) reversed in cimetidine pretreated rats. Conclusion: Cimetidine shows potential as adjunct remedy for cyclophosphamide associated nephrotoxicity. Asian Journal of Medical Sciences Vol.9(6) 2018 25-30